Objektivität und Wissen - Koch, Anton Friedrich (Zeitschrift für philosophische Forschung, 2020)
Andrea Kern has criticized the view that the fallibility of judgements is due to their objectivity and has tried to show that objective knowledge is comprehensible only if its infallibility is not logically excluded. She argues that the notion of knowledge is more fundamental than that - of error and that we must bring into play an epistemic capacity as a form of perfection to understand what knowledge is. In the present article, this position is charitably criticized and modified. It is argued that infallible knowledge is even actual, but not fully objective. Infallibility - characterises our knowledge of logical and of spatio-temporal form and our judgments of the kind "it seems to me that p". This knowledge is in neither case knowledge of particular objective facts, but in both cases knowledge of what Sebastian Rödl calls the object überhaupt - .